Study of serum calcium, phosphorus and vitamin D status in multitransfused β-thalassemia major children and adolescents of Jharkhand, India - Ahmed, Zeeshan; ., Pushpanjali; Kausar, Md. Shahnawaz; Sinha, Doyel (International Journal of Contemporary Pediatrics, 2019)
Background: The pattern of levels of calcium, phosphorous and vitamin D levels among the patients with thalassemia major undergoing repeated blood transfusions remain unexplored. Only very few studies have been undertaken among Indian population. The present study was an attempt to determine the levels of calcium, phosphorous and vitamin D levels among thalassemia major patients undergoing repeated multiple transfusions. Methods: In a prospective observational study, 65 patients suffering from β-thalassemia major, aged 2-18 years, having undergone regular blood transfusion and chelation therapy, were evaluated for the levels of serum calcium, phosphorus and vitamin D and the values were compared to the standard values of the same. Results: The mean values of serum calcium (6.72±0.66), phosphorous (5.51±1.07) and vitamin D (13.12±2.9) were significantly lower in our patients as compared to that of standard population values, the difference in each being statistically significant (p<0.05). Conclusions: It is evident from the present study that the levels of calcium, phosphorous and vitamin D are deficient among β-thalassemia major patients on repeated blood transfusion. The deficiencies may be due to iron overload or due to nutritional deficiency. Frequent monitoring and supplementation in deficient states is recommended.